Religiosity of adults on the autism spectrum: a cognitive and empirical analysis - Agnieszka Ewa Burnos; Gabriela Kopacz (Frontiers in Psychiatry, 2025)
This article presents a narrative theoretical and empirical review of religiosity in adults on the autism spectrum. Religiosity is defined as an individual set of beliefs and practices proposed by a religious institution or group. This topic is critical for better understanding the religious and spiritual needs of autistic individuals, as well as the barriers they may face in developing and practicing religiosity. Theoretical accounts of the relationship between the social and cognitive characteristics of individuals on the autism spectrum and their religious attitudes and behaviors are examined. These include theory of mind, weak central coherence, executive function deficits, restricted interests, need for predictability, cognitive rigidity, and the broken mirror hypothesis. Alongside these conceptual frameworks, the article reviews findings from nine empirical studies. The emerging picture of religiosity among autistic adults is complex and marked by inconsistency. The central hypothesis—that impairments in mentalizing reduce religiosity—has not been unequivocally supported by empirical evidence. Similarly, results regarding the overall level of religiosity and representations of God in autistic versus neurotypical individuals are inconclusive. The article offers a synthetic overview of existing hypotheses and provides recommendations for the design of future research in this area.